Strategies for mitigating heat stress and their effects on behavior, physiological indicators, and growth performance in communally managed feedlot cattle - Slayi, Mhlangabezi; Jaja, Ishmael Festus (Frontiers in Veterinary Science, 2025)
Heat stress poses a significant challenge in communal feedlot systems, affecting cattle welfare and productivity. This study evaluated the impact of shade and water-cooling interventions on thermophysiological stress reduction and growth performance in 60 cattle from communal feedlots. Physiological indicators (rectal temperature, skin temperature, respiration rate) along growth metrics (feed intake, average daily gain [ADG]) were analyzed using regression and principal component analysis (PCA) to identify key drivers of performance. The results showed a significant reduction (p < 0.05) in rectal temperature, respiration rate, and skin temperature in cattle subjected to shade and water cooling compared to the control group. Temperature-Humidity Index (THI) values frequently exceeded the heat stress threshold of 72, with peak mid-day values surpassing 80, indicating severe thermal stress. Cattle in the treated groups experienced lower THI values, reduced panting scores, and improved homeostasis under high thermal loads. Breed-specific differences were evident, with Bos indicus cattle (Nguni) maintaining lower physiological stress indicators than Bos taurus (Bonsmara), highlighting superior heat tolerance. Growth performance, measured by average daily gain (ADG) and feed conversion ratio (FCR), significantly improved in the treated groups, with ADG increasing by 18% and FCR improving by 12% relative to the control. Blood metabolite analysis revealed lower cortisol levels (p < 0.05) and improved electrolyte balance in the cooled groups, indicating reduced chronic stress and better metabolic function. Behavioral observations, recorded at 10-min intervals every 30 min, showed increased resting time and reduced panting frequency in cooled cattle, confirming enhanced thermal comfort. These findings underscore the importance of integrating cooling interventions into cattle management strategies to improve productivity and welfare in heat-stressed environments.